Reduction in hepatic endothelin-1 clearance in cirrhosis - Tran Duc, Anh Thu; Schwab, Andreas J; Simard, André; Villeneuve, Louis; Dupuis, Jocelyn (Clinical science (1979), 2003)
Circulating endothelin-1 (ET-1) levels are increased in cirrhosis. The liver is an important site for circulating ET-1 clearance through the ET(B) receptor. We evaluated ET-1 kinetics in cirrhosis to determine if a reduced liver clearance contributes to this process. Cirrhosis was induced by carbon tetrachloride in rats. Hepatic ET-1 clearance was measured in isolated perfused livers using the single bolus multiple indicator-dilution technique. Plasma ET-1 levels doubled in cirrhosis from 0.49+/-0.04 fmol/ml (mean+/-S.E.M.) to 1.0+/-0.18 fmol/ml ( P <0.01). Liver ET-1 extraction was reduced from 81+/-1% (mean+/-S.E.M.) in controls to 50+/-6% in cirrhosis ( P <0.01). Kinetic modelling revealed a major irreversible binding site for ET-1 that is blocked by the selective ET(B) receptor antagonist BQ788 and a minor non-specific reversible binding site that cannot be blocked with BQ788 or the selective ET(A) antagonist BQ123. Reduced hepatic clearance correlated with the biochemical markers of cirrhosis, portal vein perfusion pressure ( r =-0.457; P <0.001) and the increase in ET-1 levels ( r =-0.462; P =0.002). Immunohistofluorescence with specific anti-(ET(B) receptor) antibodies revealed a preponderant distribution of ET(B) receptors on hepatic stellate cells, which was increased in cirrhosis. We conclude that cirrhosis reduces ET-1 clearance probably by capillarization of hepatic sinusoids and reduced access to ET(B) receptors. This relates to the severity of cirrhosis and may contribute to the increase in circulating ET-1 levels.